Nanoindentation of Silica Colloid Thin Films - Knoke, Karen; Baker, Grace; Dunham, Douglas (My University, 2019)
Silica colloid films are technologically important as they can serve as the matrix to hold nanoparticles for the fabrication of thin film sensors. Thin film sensors need to be durable to function in a variety of environments. A Hysitron nanoindentor was used to test the hardness of three sets of silica colloid thin films. The first set was slip casted and sintered at temperatures varying by 100 C (700C-1100C). The second set was spin coated using various layer thicknesses (1-20 coats). The third set consisted of various layer thickness and gold nanoparticles with a silica matrix of various layers. Of the sintered samples our findings indicated samples sintered at higher temperatures had a higher hardness. Of the spin coated samples, it was found that the third layer, from the second set, had the highest hardness, but that could be due to an uneven spread of silica. The thickness of the first two sets were also found to observe the difference between the slip casted and spin coated samples. The spin coated samples had a thinner film. As for the samples with the gold nanoparticles we found that adding gold nanoparticles do not compromise the silica matrix.
Color poster with text, images, charts, and graphs.
Keywords: Thin film sensors; Sintering; Posters